Relational Strict Almost Contractions Employing Test Functions and an Application to Nonlinear Integral Equations - Doaa Filali; Faizan Ahmad Khan (Mathematics)
The present study deals with some fixed-point outcomes under a nonlinear formulation of strict almost contractions in a metric space endued with an arbitrary relation. The outcomes established herein enhance and develop various existing outcomes. To convince you of the infallibility of our outcomes, a few examples are presented. We apply our findings to investigate the validity of the unique solution of a nonlinear integral problem.